2016
DOI: 10.1371/journal.pone.0162381
|View full text |Cite
|
Sign up to set email alerts
|

Coping Styles and Alcohol Dependence among Homeless People

Abstract: Background and ObjectivesThe ways in which homeless individuals cope with stress may differ from those relied upon by the members of the general population and these differences may either be the result or the cause of their living conditions. The aim of the study was to determine the preferred coping style among the homeless and its relationship with alcohol dependence.MethodsThe study included 78 homeless individuals and involved the collection of demographic, sociological, psychological and medical data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…The problem of coping with stress seems to be important in the context of the development and persistence of alcohol dependence (AD) 1 1 As the study’s participants were assessed in accordance with ICD-10 alcohol dependence syndrome criteria, the term “alcohol dependence” will be used throughout the article; the equivalent of this term in the DSM 5 classification is “alcohol dependences (AD)”. and has long been raised in the literature on the subject ( Opalach et al, 2016 ). Resorting to psychoactive substances in itself can be construed as an avoidant coping strategy ( Woodhead et al, 2014 ; Mccormick et al, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…The problem of coping with stress seems to be important in the context of the development and persistence of alcohol dependence (AD) 1 1 As the study’s participants were assessed in accordance with ICD-10 alcohol dependence syndrome criteria, the term “alcohol dependence” will be used throughout the article; the equivalent of this term in the DSM 5 classification is “alcohol dependences (AD)”. and has long been raised in the literature on the subject ( Opalach et al, 2016 ). Resorting to psychoactive substances in itself can be construed as an avoidant coping strategy ( Woodhead et al, 2014 ; Mccormick et al, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…Homeless people with PAC have been found to have high rates of avoidance and emotion‐oriented stress responses . Given the previously discussed relationship between stress and PAC in homeless persons, improving coping strategies may reduce PAC.…”
Section: Resultsmentioning
confidence: 99%
“…This high prevalence of self-reported alcohol use was similar to what reported in studies implemented in other countries. A study in Poland found that 75% of homeless people in Olsztyn were dependent on alcohol (9). Another study in Madrid reported that 59% of homeless men consumed excessive alcohol at some point in their lives (18).…”
Section: Discussionmentioning
confidence: 99%
“…Homeless individuals who use alcohol and drug constitute one of the most marginalized groups in Iran (5). They are considered a high-risk population for mental health issues and alcohol consumption and substance abuse are common among them (7)(8)(9)(10). In a meta-analysis conducted by Fazel et al 29 studies with 5,684 homeless individuals were considered.…”
Section: Introductionmentioning
confidence: 99%